Insecticidal and repellent effects of tea tree and andiroba oils on flies associated with livestock - Klauck V.* (2014)
This study aimed to evaluate the insecticidal and repellent effects of tea tree, Melaleuca alternifolia (Myrtales: Myrtaceae), and andiroba, Carapa guianensis (Sapindales: Meliaceae), essential oils on two species of fly. For in vitro studies, free-living adult flies were captured and reared in the laboratory. To evaluate the insecticidal effects of the oils, adult flies of Haematobia irritans (L.) and Musca domestica L. (both: Diptera: Muscidae) were separated by species in test cages (n=10 per group), and subsequently tested with oils at concentrations of 1.0% and 5.0% using a negative control to validate the test. Both oils showed insecticidal activity. Tea tree oil at a concentration of 5.0% was able to kill M.domestica with 100.0% efficacy after 12h of exposure. However, the effectiveness of andiroba oil at a concentration of 5.0% was only 67.0%. The insecticidal efficacy (100.0%) of both oils against H.irritans was observed at both concentrations for up to 4h. The repellency effects of the oils at concentrations of 5.0% were tested in vivo on Holstein cows naturally infested by H.irritans. Both oils demonstrated repellency at 24h, when the numbers of flies on cows treated with tea tree and andiroba oil were 61.6% and 57.7%, respectively, lower than the number of flies on control animals. It is possible to conclude that these essential oils have insecticidal and repellent effects against the species of fly used in this study. © 2014 The Royal Entomological Society.